2021
DOI: 10.1186/s12877-021-02535-w
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition and other risk factors of geriatric depression: a community-based comparative cross-sectional study in older adults in rural Bangladesh

Abstract: Background Malnutrition and depression are highly prevalent in older adults and can lead to disparaging outcomes. Analytical studies on geriatric depression (GD) and its association with malnutrition are very scarce in Bangladesh, although the size of the older population is increasing fast in the country. The current study aimed to assess the association between malnutrition and depression and associated risk factors in rural older adults. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 34 publications
2
9
0
Order By: Relevance
“…Indeed, present epidemiological data suggest that deficiencies in micronutrients essential for brain metabolism, such as B vitamins, vitamins C and E, and omega-3 fatty acids, may increase the risk of depression (48) . Similar findings were made in Debre Birhan, Ethiopia (49) , in South Africa (34) , and in Bangladesh (50) . The similarity could be due to loneliness and depression, which affect food intake and increase the likelihood of being malnourished and at risk of malnutrition.…”
Section: Discussionsupporting
confidence: 83%
“…Indeed, present epidemiological data suggest that deficiencies in micronutrients essential for brain metabolism, such as B vitamins, vitamins C and E, and omega-3 fatty acids, may increase the risk of depression (48) . Similar findings were made in Debre Birhan, Ethiopia (49) , in South Africa (34) , and in Bangladesh (50) . The similarity could be due to loneliness and depression, which affect food intake and increase the likelihood of being malnourished and at risk of malnutrition.…”
Section: Discussionsupporting
confidence: 83%
“…Conversely, malnutrition has been reported to be a risk factor for depression and increased depressive symptoms [6,15,16]. A study in Bangladesh reported that malnutrition was more frequent among depressed community-dwelling participants (56.0%) than non-depressed participants [17]. This study also suggested that malnourished participants had approximately three times higher risk of depression than well-nourished participants cross-sectionally.…”
Section: Introductionmentioning
confidence: 62%
“…Also, we found a significantly higher prevalence of depressive symptoms in patients with high CONUT scores compared to other groups. Malnutrition is a recognized risk factor for the development of depression in various populations, including hospitalized patients [ 62 , 63 , 64 ]. Recently, a significant association between CONUT score and risk of depression was observed in patients hospitalized for acute ischemic stroke [ 65 ].…”
Section: Discussionmentioning
confidence: 99%